Penerapan Lima Pilar STBM Terhadap Kejadian Stunting - Muslimin B; Ruqaiyah Ruqaiyah; Ali Imran; Suhartini Suhartini (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Stunting cases in Maros Regency decreased from 3812 cases or 13.04% in 2020 to 2892 cases or 9.47%, but in 2022 the opposite happened, namely a significant increase in the number of cases and the prevalence of cases increased to 3750 cases or 12 .82%. In Tompobulu District, stunting cases have decreased from 12.69% in 2020, down to 12.11% in 2021. And in 2022 it will fall to 9.69%. Therefore, in this research we will analyze the relationship between the five STBM pillars and stunting cases in Tompobulu District, Maros Regency. The type of research in this research is research using a survey with a Cross Sectional Study approach. The population in this study were all stunted toddlers who were examined, totaling 146 toddlers. The sample in this research is the entire population. The results of the research show that there is a relationship between CTPS (0.005), drinking water and food management (0.005), securing RT waste (0.000), and securing liquid waste (0.000) with the incidence of stunting. Meanwhile, stopping defecation has no relationship with the incidence of stunting (0.911). The conclusion of this study is that the 4 variables in the study have a relationship with the occurrence of stunting. It is recommended that local communities increase awareness of the importance of sanitation in their area in order to reduce the high stunting rate.  Keywords: 5 Pillars, Community Based Total Sanitation (STBM), Stunting